Determination of boiled wort colour: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Angelino, S. A. G. F. (BrewingScience, 2000)
A method for the determination of boiled wort colour has been collaboratively tested by the Analysis Committee of the European Brewery Convention. In this trial the 14th EBC Standard Malt and two commercial malts were tested by 21 laboratories. Repeatability (r₉₅) and reproducibility (R₉₅) values of 0.33 – 0.42 and 1.12 – 1.44 EBC units were obtained respectively at a mean level of 4.7 – 5.2 EBC units. At a mean level of 8.9 EBC units these respective values were 0.44 and 2.25 EBC units. The data sets could be split into two sub-sets for laboratories using either the included heating plate boiling procedure or the glycerol/ oil bath boiling procedure. Statistical analysis of both sub-sets revealed that reproducibility is unambiguously better for the glycerol/oil bath procedure at all levels. For repeatability the situation is less clear. The evaluated method is recommended for inclusion in Analytica-EBC.